6(11+s)=96

Simple and best practice solution for 6(11+s)=96 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(11+s)=96 equation:


Simplifying
6(11 + s) = 96
(11 * 6 + s * 6) = 96
(66 + 6s) = 96

Solving
66 + 6s = 96

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-66' to each side of the equation.
66 + -66 + 6s = 96 + -66

Combine like terms: 66 + -66 = 0
0 + 6s = 96 + -66
6s = 96 + -66

Combine like terms: 96 + -66 = 30
6s = 30

Divide each side by '6'.
s = 5

Simplifying
s = 5

See similar equations:

| 7x-(5+6x)=4 | | -24=12v | | 12(z-7)=60 | | z^3+24z^2-648=0 | | 125=5(3+x) | | 3(z-1)+8=14 | | 32y+10-2=24 | | -4(9g)=252 | | 15=3.5s-2s | | 0.3x-15=0.2x-5 | | 8k+7-3k=14k+10 | | 7t-t=54 | | 51=15y+2y | | 4.8=1.8n+.6n | | 6y+1=5y-8 | | 18=8a-5a | | 2x+6x=24 | | 2r-21.6=3r+36 | | 3.2x-1.2x=8 | | 13u=-65 | | 6+10x-4-6x=-22 | | 8x+4y=36.12 | | x-36=-2 | | 6+10x-4-6x=22 | | 2x^2-9x+13=0 | | 0=2x^4+20x^2+18 | | 9+x-4=2 | | .5x+1.5x=12 | | 0.97+a=2.6 | | Y-95=5 | | 24w^5-15w^3+15w^2= | | 3x^4-6x^3+2x-4=0 |

Equations solver categories